Biodegradation of Agricultural Waste by Microfungi: An Eco - Friendly Approach - Kanagaraj, Kavinmuhil (Journal of Research in Science and Engineering, 2025)
Agricultural waste management is an increasing environmental concern, and microbial biodegradation offers a sustainable solution. Micro fungi are known for their ability to break down complex organic materials, converting waste into valuable byproducts such as bio fertilizers and bioactive compounds. This paper examines the efficiency of different micro fungal species in decomposing agricultural residues, focusing on enzymatic activity, decomposition rates, and environmental factors influencing fungal biodegradation. The findings highlight the potential of micro fungi to reduce waste accumulation, enhance soil health, and promote nutrient recycling. By understanding the interactions of fungi with agricultural waste, sustainable waste management practices can be improved to minimize environmental impact and support circular agriculture.